Frequency, Etiology and Leading Causes of Pre-Senile Cataract: A Descriptive Study - Uzma Ali Kant , Maria Zubair , Fuad A K Niazi , Qamar Farooq , Sumra Munir , Seher Umer, (Journal of Rawalpindi Medical College, 2021)
Background: Cataract is generally caused due to physical aging, but in some cases, there are chances that it may develop in early ages (Pre-senile cataract). Pre-senile cataract is believed not to be primary in nature and some underlying ocular/systemic/environmental factor is causing the lens opacification at an early age. This study aim was to determine frequency and risk factors of pre-senile cataract in our population Methods: this observational study at Outdoor Patient - Eye in Benazir Bhutto Hospital, Rawalpindi (BBH), for the period from December 2017 to June 2018. Cataract was diagnosed on slit lamp examination. Detail history, Ocular and systemic examination was done for all pre-senile cataract cases. Laboratory/radiological investigations were performed when and where required. Using the Excel spreadsheet, Statistical analysis of descriptive data was carried out. Results: A total of 11448 patients were examined, whereby cataract was found in 849 (7.41%) patients. Out of these 849, 165 (19.43%) cases were pre-senile cataract. Pre-senile cataract was most seen in age group 30-49 86 (52.13%) and among women 93 (56.36%). The identified causes were idiopathic 55 (33.3%), diabetes 45(27.3%) and Steroids and other drugs related 33 (20.0%). posterior sub-capsular cataract is 60(36.36%) was most identified type in the study among pre-senile cataract.